Persuasive technology for improving information security awareness and behavior: literature review - Bawazir, Mohammed Abdullah; Mahmud, Murni; Abdul Molok, Nurul Nuha; Ibrahim, Jamaludin (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The use of Persuasive Technology in various fields is rapidly increasing. It can be applied in many fields such as computing, marketing, sales, environment, education, and health. Persuasive Technology has been found effective in bringing a required change in users' behaviors and attitudes. However, the use of persuasive technology is scarce in the field of Information Security awareness. This paper reviews extensive literature review which focuses on a perspective on how to create awareness among users for good information security practices by applying Persuasive Technology techniques and approaches. The conceptual findings suggest there is a tremendous potential of Persuasive Technology to be applied to persuade users to change their behavior and perception toward Information Security practices.